2019
DOI: 10.1101/19006429
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inferring the role of the microbiome on survival in patients treated with immune checkpoint inhibitors: causal modeling, timing, and classes of concomitant medications

Abstract: The microbiome has been shown to affect the response to Immune Checkpoint Inhibitors (ICIs) in a small number of cancers. Here, we sought to more broadly survey cancers to identify those in which the microbiome will play a role using retrospective analyses. We created a causal model for the relationship between medications, the microbiome and ICI response and used it to guide the abstraction of electronic health records of 690 patients who received ICI therapy for advanced cancer. Medications associated with c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 43 publications
1
25
0
Order By: Relevance
“…CS use during these later CPI treatment periods may have different biological implications and different underlying reasons, such as management of immune-mediated adverse events. 18 , 23 Our findings are consistent with recent reports of clinical outcomes associated with CPI treatment and bCS use in many of the same tumor types, including shorter OS and/or progression-free survival (PFS) in patients who received concomitant CSs with CPI 20 22 , 27 , 30 , 38 , 39 – although some differences have emerged in smaller study populations or subgroups, such as those receiving CSs related versus unrelated to cancer care. 24 , 30 , 38 …”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…CS use during these later CPI treatment periods may have different biological implications and different underlying reasons, such as management of immune-mediated adverse events. 18 , 23 Our findings are consistent with recent reports of clinical outcomes associated with CPI treatment and bCS use in many of the same tumor types, including shorter OS and/or progression-free survival (PFS) in patients who received concomitant CSs with CPI 20 22 , 27 , 30 , 38 , 39 – although some differences have emerged in smaller study populations or subgroups, such as those receiving CSs related versus unrelated to cancer care. 24 , 30 , 38 …”
Section: Discussionsupporting
confidence: 89%
“…Nevertheless, six studies consistently reported significantly shorter OS and PFS with CS use during CPI treatment in final or multivariable models adjusting for baseline characteristics and conditions (Table S4). 20 22 , 26 , 27 , 39 Spakowicz and colleagues evaluated the effect of five types of concomitant medications (antibiotics, CSs, proton pump inhibitors, histamine 2 blockers, and non-steroid anti-inflammatory drugs) on OS among 690 CPI-treated patients with advanced/metastatic melanoma (29%), NSCLC (23%), or other cancers. Multivariate HRs showed associations of OS with CS use within 28 days of the CPI start date for patients with melanoma (HR, 1.57; P = .01) or NSCLC (HR, 1.85; P < .01).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations